Online Shopping Behavior of Students in Kathmandu - Manandhar, Raju Bhai (Nepal Journal of Multidisciplinary Research, 2021)
Online shopping is a form of electronic commerce which allows consumers to directly purchase products or services from seller over the internet using web browser. The main objective of this study is to investigate the factors affecting online shopping behaviors of students in Kathmandu. The research adopted the descriptive research design. The method of convenience sampling method was used while selecting the samples. There was total 50 students were selected for this study from different college of Kathmandu. Statistical software was used to analyze the data. The study found that ‘security’ was perceived to be highest and most influential factor of online shopping behavior whereas ‘price’ was perceived as second most important influential factor, and ‘convenience’ was perceived to be least important factor influencing the online shopping behavior of the students in Kathmandu. The future researcher can study the shopping behaviour of general public having with a larger sample size.